Atlas of the year 1000 - Man, John (Harvard University Press, 1999)
As we enter the new millennium, with the expected retrospectives, this book provides a fascinating look at the end of the previous millennium. Man, a historian and travel writer, renders an engaging account of the world in the year 1000. He notes the first millennial fears, when much unchartered territory still existed in the world, and cites archaeological and anthropological evidence of more developed societies in Africa and the Americas than had been previously acknowledged: highly developed cities before the introduction of European influences. He explores how factors such as different types of crops and animals caused different speeds of development in the civilization of Europe versus the Americas. Man examines Europe's threat to the more developed societies of Islamic nations and simmering conflicts throughout Europe that despite the religious veneer were more about power. The book is beautifully illustrated with maps and photographs of artifacts and includes arresting sidebars on politics, religion, literature, and economics that influenced events of the last millennium